Microbuses and Mobile Homemaking in Exile: Sudanese Visiting Strategies in Cairo - Fábos, Anita (Refuge: Canada's Journal on Refugees, 2015)
Paying home visits to mark social events and maintain networks is an established cultural pattern in Arab countries. Northern Sudanese displaced in Cairo in the 1990s made significant efforts to continue visiting each other in their temporary homes, despite having to travel long distances to members of their widely scattered networks. The deterioration of the legal and political status of Sudanese living in Egypt during the 1990s contributed to longer-term uncertainty for those who sought safety and security in Cairo. In this article, I argue that this long-term uncertainty constitutes a protracted refugee situation, and that Sudanese visiting practices constituted a mobile homemaking strategy that actively contributed to the negotiation of a complex ethnic identity in their protracted exile. Ranging across space and connecting people through experiences and values of Sudanese “homeyness,” visiting during these fraught years connected individuals and networks into constellations that recreated familiar patterns of homemaking but also encouraged new meanings granted to homeland and belonging. Woven through the more familiar relationship between “home” and “away” were the policy positions about urban refugees taken by the Egyptian government, United Nations High Commission for Refugees, International Organization for Migration, and other humanitarian aid and resettlement agencies, which produced a state-centred view of “home” for Sudanese.